2017
DOI: 10.1177/2331216517744675
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cognitive Performance and Speech-in-Noise Perception for Adult Listeners: A Systematic Literature Review and Meta-Analysis

Abstract: Published studies assessing the association between cognitive performance and speech-in-noise (SiN) perception examine different aspects of each, test different listeners, and often report quite variable associations. By examining the published evidence base using a systematic approach, we aim to identify robust patterns across studies and highlight any remaining gaps in knowledge. We limit our assessment to adult unaided listeners with audiometric profiles ranging from normal hearing to moderate hearing loss.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
153
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(191 citation statements)
references
References 106 publications
16
153
4
3
Order By: Relevance
“…There was a nonsignificant trend relating the WASI Perceptual Reasoning Index to sentence recognition, which had approximately the same effect size as previously reported relationships between other tests of fluid intelligence and vocoded speech (O'Neill et al, 2019). Previous research has found weak correlations between speech recognition and various cognitive subscales (Dryden et al, 2017), which may reflect the general association between fluid intelligence and speech recognition. Our results suggest that serial recall is a more proximal test of the skills necessary to perform vocoded sentence recognition.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…There was a nonsignificant trend relating the WASI Perceptual Reasoning Index to sentence recognition, which had approximately the same effect size as previously reported relationships between other tests of fluid intelligence and vocoded speech (O'Neill et al, 2019). Previous research has found weak correlations between speech recognition and various cognitive subscales (Dryden et al, 2017), which may reflect the general association between fluid intelligence and speech recognition. Our results suggest that serial recall is a more proximal test of the skills necessary to perform vocoded sentence recognition.…”
Section: Discussionsupporting
confidence: 72%
“…The nonauditory variability in vocoded sentence recognition was primarily explained by individual variability in serial recall ability (see Figure 5). The strength of this relationship was stronger than typically observed between working memory tasks and speech recognition in noise (Dryden et al, 2017), even for working memory tasks that use auditory stimuli (S. L. Smith et al, 2016). There are several theoretical explanations that could account for this relationship.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The relationship between speech recognition threshold (SRT) and working memory capacity (WMC) has been well-established (denoted as WMC-SRT relationship in this article), and has been found robust in listeners with and without hearing loss (e.g. Petersen et al 2016;Gordon-Salant and Cole 2016;Ng et al 2014;; more examples, (Gatehouse and Gordon 1990;Davis 2003;Gatehouse, Naylor, and Elberling 2003;Lunner 2003;Foo et al 2007;Lunner and Sundewall-Thor en 2007;Moore 2008;Rudner et al 2009;Rudner, R€ onnberg, and Lunner 2011;Picou, Ricketts, and Hornsby 2013;Dryden et al 2017). However, the general picture may have to be nuanced after a recent meta-analysis by (F€ ullgrabe and Rosen 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Some participants improved relative to the baseline (XYZ) condition, whereas other participants performed more poorly when the masker was repeated. We collected working memory and inhibitory control measures, which have been shown to correlate with speech perception in noise in prior research (for review see Dryden et al 2017;Akeroyd 2008), but these did not correlate with overall performance, nor with the repetition advantage. Nonetheless, the results suggest that some stable di↵erence or di↵erences among participants makes the repetition of the noise pattern beneficial for some and detrimental to others.…”
Section: Discussionmentioning
confidence: 99%